The Evaluation Of The Performance Of The Automatic Exposure Control System Of Some Selected Mammography Facilities In The Greater Accra Region, Ghana - Amesimenu, R. (University of Ghana, 2013)
Mammography aids in the early detection of breast cancer. X-rays has an associated risk of inducing cancer though very useful and as such mammography procedures should be optimized through the appropriate processes such as the selection of exposure factors for an optimum image and minimal dose to patients. The automatic exposure control (AEC) aids in the selection of exposure factors thus controlling the amount of radiation to the breast and automatically compensates for differences in breast thickness and density. The performance of the automatic exposure control system of mammography equipment and the status of quality management systems including quality assurance and quality controls of four (4) mammography facilities within the Greater Accra Region were assessed. In assessing the performance of the automatic exposure control system, the short term reproducibility test, thickness and voltage compensation tests were carried out using breast equivalent phantom of various thicknesses. Half value layer test, film reject analysis and patient dose assessment were also performed. Analysis of the responses of the questionnaire administered to radiographers and supervisors of the selected facilities revealed that three (3) of the facilities have some aspect of a quality management system programme in place but not effectively implemented. Measured optical densities from the various tests performed to evaluate the performance of the automatic exposure control systems revealed that the AEC compensates for the different phantom thicknesses and tube voltages (kV) by producing comparable optical densities for the various phantom thicknesses and tube voltages. Some of the measured optical densities were within the recommended optical density range of 1.5 OD – 1.9 OD. The highest optical density value was 0.13 OD above the highest limit of 1.9 OD. The film reject analysis showed that patient motion accounted for the larger part (28 %) of film rejects. Other factors such as too light or too dark films also accounted for film reject signifying the need for continuous training for radiographers and an effective quality control programme. Estimated mean glandular dose (MGD) of values 1.0 mGy, 1.3 mGy, 1.1 mGy and 1.1 mGy at 28 kV for the selected facilities were less than 2 mGy and 3 mGy per the recommendation of International Atomic Energy Agency (IAEA) and American College of Radiology (ACR) respectively. Management of mammography facilities must establish an effective quality management system which must be implemented and continually improved to enhance radiological services delivered to patients as well as improve the radiation protection of patients.
Thesis (MPhil)
Keywords: Performance Evaluation; Automatic Exposure Control System; Mammography Facilities; Greater Accra Region; Ghana